Catheter ablation of atrial fibrillation in patients with concomitant sinus bradycardia: Insights from the German Ablation Registry - Zylla, Maura Magdalena; Brachmann, Johannes; Lewalter, Thorsten; Hoffmann, Ellen; Kuck, Karl-Heinz; Andresen, Dietrich; Willems, Stephan; Hochadel, Matthias; Senges, Jochen; Katus, Hugo; Thomas, Dierk (Journal of electrocardiology, 2016)
Aims - This investigation addresses procedural characteristics of catheter ablation in patients with atrial fibrillation (AF) and sinus bradycardia. - Methods - From the prospective, multi-center German Ablation Registry 1073 patients with sinus rhythm at the time of AF ablation were divided into two groups according to heart rate at start of procedure (A, <60 beats per minute (bpm), n=197; B, 60-99bpm, n=876). - Results - Acute procedural success was high (≥98%) and similar between groups. Procedure duration and energy application time were increased in group A (180min vs. 155min and 2561s vs. 1879s, respectively). Major complications were more frequent in group A (2.2% vs. 0.5%), and a greater proportion of these patients was discharged under antiarrhythmic medication (64% vs. 52%). - Conclusion - Catheter ablation of AF with concomitant sinus bradycardia is associated with high procedural efficacy, longer procedure- and energy application durations, and a slightly elevated complication rate.